2018
DOI: 10.5534/wjmh.180028
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anion Production by the Spermatozoa of Men with Varicocele: Relationship with Varicocele Grade and Semen Parameters

Abstract: PurposeTo investigate the pathophysiological role of superoxide anion and total reactive oxygen species (ROS) production by the spermatozoa of men with varicocele and its relationship with varicocele grade and semen parameters.Materials and MethodsThis prospective study included 34 men with grade II–III varicocele, regardless of their fertility status. The control group consisted of 13 healthy men. Semen characteristics were examined according to the 2010 World Health Organization criteria. The swim-up method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
2
12
0
3
Order By: Relevance
“…These studies suggest that ADR has direct inhibitory effect on androgen biosynthesis in Leydig cells. The significant reduction in sperm count and motility might be due to increase in toxin ROS which is a crucial factor in sperm DNA fragmentation and sperm motility [24, 25]. This study also demonstrates that DA-9401 can improve sperm count, sperm motility, and serum testosterone level.…”
Section: Discussionmentioning
confidence: 64%
“…These studies suggest that ADR has direct inhibitory effect on androgen biosynthesis in Leydig cells. The significant reduction in sperm count and motility might be due to increase in toxin ROS which is a crucial factor in sperm DNA fragmentation and sperm motility [24, 25]. This study also demonstrates that DA-9401 can improve sperm count, sperm motility, and serum testosterone level.…”
Section: Discussionmentioning
confidence: 64%
“…Also, Mostafa, Anis, Nashar, Imam, and Osman () pointed to the significant increase of seminal plasma OS in cases associated with higher varicocele grades. Lately, Alkan et al () showed higher superoxide anion and total seminal ROS levels in varicocele grade III cases compared with grade II cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our work indicated that formalin declined sperm motility. As stated by Alkan and colleagues immotile and atypical sperm are able to generate superoxidase, which has an oxidizing effect can decline the sperm quality like motility (43).…”
Section: Discussionmentioning
confidence: 94%